Emergence and management of drug-resistant enterococcal infections (2008)
The treatment of multidrug-resistant enterococcal infections continues to be a challenge for clinicians. Glycopeptide and beta-lactam resistance is now a common feature of the majority of Enterococcus faecium hospital isolates, and resistance to aminoglycosides, quinupristin-dalfopristin, linezolid and daptomycin further complicates the problem. New antibiotics, such as tigecycline, lipoglycopeptides (dalbavancin, oritavancin and telavancin) and cephalosporins with activity against Enterococcus faecalis (ceftobiprole and ceftaroline), may have potential activity against certain resistant enterococcal strains in specific clinical settings, as may some older antibiotics, such as ampicillin, chloramphenicol, doxycycline, minocycline and nitrofurantoin. However, the treatment of endovascular infections (particularly endocarditis, where bactericidal therapy is important for optimal cure rates) caused by resistant enterococci continues to be an immense challenge even with the availability of new agents. The optimal therapy for these infections is not well established and clinical data are usually limited to case reports with conflicting results. Therefore, treatment decisions may have to be based on animal models and sporadic experiences and the best approach is for the physician to consider carefully each patient on a case by case manner and gather all the clinical and microbiological information possible regarding species identification and susceptibilities in order to choose a therapeutic regimen that would appear to be active.